On the potential balance among compulsory education outcomes through econometric and multiobjective programming analysis - Luque, M.; Marcenaro-Gutiérrez, O.D.; López-Agudo, L.A. (European journal of operational research, 2015)
•Better understanding of factors to achieve optimal educational outputs.•We analyze teacher-based assessments in three different subjects using the multiobjective methodology.•A reference point approach is used to determine the profile of the most “successfully-balanced” students.•The profile of the most balanced-productive students in Andalusia depends on the students' gender.•Parents’ education and students' effort are key to optimal and balanced educational performance. This paper sheds new light on the relationship between inputs and outputs in the framework of the educational production function. In particular, it is geared at gaining a better understanding of which factors may be affected in order to achieve an optimal educational output level. With this objective in mind, we analyze teacher-based assessments (actual marks) in three different subjects using a multiobjective schema. For much of the analysis we use data from a recent (2010) Survey – ESOC10, linked with the results from an educational assessment program conducted among 11 and 15 year-old students and with the administrative records on teacher-based scores. Following the statistical and econometric analysis of these data, they are used to build a multiobjective mixed integer model. A reference point approach is used to determine the profile of, potentially, the most “successful and balanced” students in terms of educational outcomes. This kind of methodology in multiobjective programming allows generating “very balanced” solutions in terms of the objective values (subjects). Finally, a sensitivity analysis is used to determine policies that can be carried out in order to improve the performance levels of primary and secondary education students. Particularly, policy makers should be more concerned with the need to promote some cultural habits – such as reading –, from both the students’ and parents’ side. Additionally, policy efforts should be focused on making the vocational pathways available to Spanish youth more appealing, with the aim of taking advantage of the particular skills of students not succeeding in the academic track.